A comparative study on dynamic stiffness in typical finite element model and multi‐body model of C6–C7 cervical spine segment. (3rd December 2015) - Wang, Yawei; Wang, Lizhen; Du, Chengfei; Mo, Zhongjun; Fan, Yubo
Summary: In contrast to numerous researches on static or quasi‐static stiffness of cervical spine segments, very few investigations on their dynamic stiffness were published. Currently, scale factors and estimated coefficients were usually used in multi‐body models for including viscoelastic properties and damping effects, meanwhile viscoelastic properties of some tissues were unavailable for establishing finite element models. Because dynamic stiffness of cervical spine segments in these models were difficult to validate because of lacking in experimental data, we tried to gain some insights on current modeling methods through studying dynamic stiffness differences between these models. A finite element model and a multi‐body model of C6–C7 segment were developed through using available material data and typical modeling technologies. These two models were validated with quasi‐static response data of the C6–C7 cervical spine segment. Dynamic stiffness differences were investigated through controlling motions of C6 vertebrae at different rates and then comparing their reaction forces or moments. Validation results showed that both the finite element model and the multi‐body model could generate reasonable responses under quasi‐static loads, but the finite element segment model exhibited more nonlinear characters. Dynamic response investigations indicated that dynamic stiffness of this finite element model might be underestimated because of the absence of dynamic stiffen effect and damping effects of annulus fibrous, while representation of these effects also need to be improved in current multi‐body model. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A finite element model and a multi‐body model of C6–C7 cervical spine segment were established using available material data and typical modeling technologies. Dynamic stiffness was markedly different between the finite element model and the multi‐body model because different methods were used to include viscoelastic properties and dynamic effects of intervertebral disc. The results showed that dynamic stiffen effect and damping effect of annulus fibrous were keys for improving current modeling methods.